Technical opportunities for sustaining wheat productivity growth toward 2020 - Pingali, Prabhu; Rajaram, Sanjaya (International Food Policy Research Institute, 1998)
The Green Revolution has had a tremendous positive effect on food security in the developing world. Increased use of modern varieties of wheat has helped belie the conventional wisdom of the 1970s that the world was going to run out of food. But IFPRI projections indicate that global demand for wheat will rise by 40 percent by 2020, and the resources available for wheat production will significantly diminish. For the first time since the beginning of the Green Revolution, there are serious concerns about future wheat supply. In meeting projected demand, researchers and policymakers must recognize that global food markets are becoming increasingly integrated, agricultural resources devoted to crop production are being diverted, and research systems are facing declining budgets. Given the steady rise in wheat demand due to population and income growth, wheat productivity growth over the next two decades must at least match the rate observed over the past three decades if the increased wheat demand projected by IFPRI is to be met. These production increases must come from favorable, as well as marginal, production environments. In high-potential and irrigated environments, shifting the yield frontier while improving input use efficiency are the priorities for research. In the case of marginal environments, improved tolerance to physical stresses will continue to be the priority. Innovations in crop and resource management will be important from the viewpoint of productivity and sustainability in both the high-potential and low-potential environments. Continued success in wheat germplasm and technology dissemination worldwide depends on the free and uninhibited flow of genetic materials and information. Restrictions imposed on such movement due to intellectual property protection could have serious consequences on the ability of developing countries to sustain wheat productivity growth.